Design And Construction Of A Web-Based Point Of Sale Application For The Bakso Cirawang Rayu Business Using The Extreme Programming Method - Katresna Asterina Latifa; Yudhi Raymond Ramadhan; Muhammad Rafi Muttaqin (CV. AFDIFAL MAJU BERKAH, 2026)
Manual transaction management in culinary MSMEs still causes various obstacles, such as recording errors, transaction calculations, and sales data management. This study aims to design and build a web-based Point of Sale (POS) application at Bakso Cirawang Rayu using the Extreme Programming method. This study uses the Extreme Programming (XP) method in application development. The scope of the study focused on the process of recording orders, sales transactions, transaction history, sales reports, and estimating soup availability. The research instruments were in the form of interview guidelines, observations, and literature studies. Data were analyzed descriptively to identify user needs as a basis for system design. The results showed that the application was successfully developed with login features, dashboards, menu management, cashier management, sales transactions, reports, and soup availability estimation. Test results showed that all features functioned according to their functions, thus supporting the transaction process and sales data management. In conclusion, the web-based POS application developed using Extreme Programming was able to improve operational efficiency, reduce human error, and assist decision making at Bakso Cirawang Rayu.